Aplikasi Pengenalan Budaya Jawa Tengah menggunakan Virtual Reality Berbasis Android - Rudolf Dekha Silaen; Apri Junaidi; Ely Purnawati (Research Group of Data Engineering, Faculty of Informatics, 2021)
At this time, it is very difficult to introduce culture to students in school, and this is also involved to children do not recognizing their own culture. Many schools have so limited funds to go to museums or cultural performances, especially school which are far from the capital city. Therefore, it is necessary to make an android-based application using Virtual Reality. This writing describes about a method of designing and making Central Javanese cultural learning-application for elementary and secondary school students by utilizing technological developments, one of the fields is education. In the field of education, Virtual Reality can be used as a learning media which is able to make it more attractive. This Virtual Reality technology can be applied in regional cultural learning systems, one of this is the introduction of Central Javanese culture. The use of Virtual Reality technology is expected to be able to display objects in the form of musical instruments, traditional clothes, traditional houses, paintings and traditional weapons in virtual 3D using images which can used to be markers. This making of cultural learning application using Unity, Blender, and SketchUp. The development of this application uses the waterfall model where this method pays close attention to the design of the analysis, design, implementation and testing. With this research, it is hoped that it can help students in Central Java to get to know their culture. This application is specified for students specifically for elementary and secondary schools based on Android. This application is expected to be used as an interactive alternative media besides books, so it’s able to make students more interest on learning Central Javanese culture. This application will be made by using Unity and other assistive software and finally it will be refined with VR Box hardware to make it more real. Keywords: Virtual Reality, Unity, Budaya, Blender, SketchUp, Waterfall.